Air variability in maxillary sinus during radiotherapy for sinonasal carcinoma. (March 2021) - Sharma, M.B.; Argota Perez, R.; Holm, A.I.S.; Korreman, S.S.; Jensen, K.; Elstrøm, U.V.; Grau, C.
Highlights: Air volume in the ipsilateral maxillary sinus varies substantially during a RT treatment course. Aeration changes cannot be predicted from evaluation of changes in the first five fractions. No conclusive dosimetric consequences of aeration changes are present for photon or proton therapy. Abstract: Introduction: The aim was to characterise patterns and predictability of aeration changes in the ipsilateral maxillary sinus during intensity-modulated radiotherapy (IMRT) for sinonasal cancer (SNC), and in a sample evaluate the dosimetric effects of aeration changes for both photon and proton therapy. Materials and methods: The study included patients treated with IMRT for SNC in a single institution in 2009–2017. The volume of air in the ipsilateral maxillary sinus was recorded in 1578 daily cone beam computer tomography (CBCT) from 53 patients. Patterns of changing air volumes were categorised as ' stable ', increasing ', ' decreasing ', or ' erratic '. For the prediction analysis, categorisation was performed based both on the entire treatment course and the first five fractions (F1–5). Photon and proton therapy plans were generated for four patients, the one from each category with the largest aeration variation. Synthetic CT images were generated for each CBCT and all plans were recalculated on the daily synthetic CTs. Results: The absolute volume of air varied considerably during the treatment course, ranging from 0 to 25.9 cm 3 . Changes within a single participant varied in the range of 0–18.7 cm 3 . In the categorisation of patterns, most patients had increasing aeration of the sinus. Generally, patterns of aeration could not be predicted from F1–5. Patients categorised as increasing in F1–5 had the best prediction, with 78% predicted correctly as increasing for the entire treatment course. The numeric correlation coefficients for target coverage and air volume were low for 3/4 scenarios (photons 0.03–0.23, protons 0.26–0.48). No straightforward correlation between the dosimetric effect and the volume changes could be detected in the sample test of four patients for neither photon nor proton therapy. Conclusion: The variation of aeration was large and unpredictable. No clear dosimetric consequences of the aeration variation were evident for neither IMRT nor proton therapy for the patients investigated.